'घामको चुम्बन’ मा पर्यावरण - Ghimire, Sachitananda (Janabhawana Research Journal, 2025)
The present study examines Yubaraj Nayaghare's travelogue Ghamko Chumban (Kiss of the Sun) ecologically from postmodern critical theory paradigms. Post-Rachel Carson's Silent Spring (1962), there is environmental concern in literature, and today the environment is thought of as an inter-disciplinary field. A descriptive analytical method is employed by the research to examine environmental theory, which theoretically examines the local environment. To maintain objectivity and genuineness, the article follows a research-based approach derived from theoretical research. In Kiss of the Sun, there is a critical examination conducted particularly on the nature, form, metamorphosis, rot, and destruction of the environment using library-based research methods. The narrative consists of Nepal's natural environment and its social, cultural, linguistic, musical, literary, and disaster-related contexts, capturing the Nepali identity as presented in the work. During the research, literary analysis is employed as the primary method of analyzing the story. The article concludes that this book is a fine example of how diverse aspects of Nepal's surroundings can be presented within one literary piece.